Patricia Moya, El principio del conocimiento en Tomás de Aquino. EUNSA. Pamplona 1994. 290 páginas. - Massini Correas, Carlos I. (1999)
Fil: Massini Correas, Carlos I. Universidad de Mendoza; Argentina